The need to develop a successful competition regime in Uganda: an analysis of the factors hindering the operationalisation and implementation of the East African Community Competition Act - Nansubuga, Catherine (Department of Commercial Law, 2016)
Uganda is in the process of enacting a competition law. Like most developing countries, it faces a unique adoption process, local circumstances and concerns that makes the competition law and enforcement practices distinguishable from other jurisdictions. This research will analyse the need for development of a successful competition regime in Uganda by highlighting the factors that should inform the law and policy. The study will analyse the adequacy of the current competition bill 2004 in comparison with the competition laws of Kenya, Tanzania and South Africa and propose that Uganda needs to develop a competition regime that is suited to its local development needs. The East African Community (EAC) aimed at enhancing trade liberalisation and development, among other sectors adopted the East African Competition Policy in 2004 and subsequently the East African Legislative Assembly enacted the East African Competition Act in 2006. However to date an East African Community Competition Authority has not been established and the law is not yet operational. The study will further appraise the challenges to the operationalisation and implementation of the East African Community Competition Act and suggest that apart from the fact that Uganda has not enacted a competition law as required by the East African community Protocol, there are other significant challenges hindering the operationalisation and implementation of the East African Community Competition Act.